Search for new particles in final states with a boosted top quark and missing transverse momentum in proton-proton collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sauer, Christof; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (Journal of high energy physics, 2024)
A search for events with one top quark and missing transverse momentum in the final state is presented. The fully hadronic decay of the top quark is explored by selecting events with a reconstructed boosted top-quark topology produced in association with large missing transverse momentum. The analysis uses 139 fb−1 of proton-proton collision data at a centre-of-mass energy of √s = 13 TeV recorded during 2015-2018 by the ATLAS detector at the Large Hadron Collider. The results are interpreted in the context of simplified models for Dark Matter particle production and the single production of a vector-like T quark. Without significant excess relative to the Standard Model expectations, 95% confidence-level upper limits on the corresponding cross-sections are obtained. The production of Dark Matter particles in association with a single top quark is excluded for masses of a scalar (vector) mediator up to 4.3 (2.3) TeV, assuming mχ = 1 GeV and the model couplings λq = 0.6 and λχ = 0.4 (a = 0.5 and gχ = 1). The production of a single vector-like T quark is excluded for masses below 1.8 TeV assuming a coupling to the top quark κT = 0.5 and a branching ratio for T → Zt of 25%.
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, D.F. Rassloff, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, M. Wessels, J. Zinsser [und 2916 weitere]
Gesehen am 02.05.2025